Cybercrime: Challenges and Solutions in Law Enforcement in The Digital Era - Muh Fadli Faisal Rasyid (Proceeding of the International Conference on Law and Human Rights, 2024)
This study aims to provide a comprehensive understanding of cybercrime and to propose actionable strategies that strengthen law enforcement's response in an increasingly digital world. The study systematically analyzes existing legal frameworks and enforcement strategies to assess their efficacy in addressing these complex crimes. It highlights the gaps in legislation and the limitations of current technological capabilities that hinder effective law enforcement. By addressing these challenges collaboratively, law enforcement can enhance its effectiveness in safeguarding society against the evolving landscape of cyber threats. Enforcement agencies in combating it. It examines the types of cybercrimes prevalent in the digital era, including hacking, identity theft, and online fraud. The study evaluates the effectiveness of current legal frameworks and law enforcement strategies in addressing these crimes. Additionally, it proposes solutions to enhance collaboration between international agencies, improve technological capabilities, and raise public awareness about cyber threats, aiming to strengthen the response to cybercrime. Additionally, raising public awareness about cyber threats is crucial for prevention. The research advocates for educational campaigns that inform citizens about the risks and protective measures related to cybercrime.